Association of periodontitis and tooth loss with extent of coronary atherosclerosis in patients with type 2 diabetes mellitus - Shen, Minhua; Li, Zhen; Li, Huizhi; Yan, Xinfeng; Feng, Bo; Xu, Lei (Frontiers in Endocrinology, 2023)
To investigate This study explores the association betweenof the parameters of periodontitisal disease and tooth loss with the extent of diabetic coronary atherosclerosis. and the predictive value of oral microbial communities and salivary inflammatory factors. Materials and methods: 272 patients, who hospitalized in Shanghai East hospital and received coronary artery calcium (CAC) CT scan, were enrolled to this study. Individuals were grouped based on their CAC scores, as normal to mild coronary atherosclerosis (AS) group (0 ≤ scores ≤ 100, n=184) , and moderate to severe group (≥101,n=88). Parameters of periodontitis Oral parameters and missing teeth were evaluated for every patient. The severity of periodontitisOral status was categorized as mild, moderate, and severe group. The taxonomic composition of the microbiota was determined by using full-length 16S ribosomal RNA gene sequencing. Salivary inflammatory factors were tested by ELISA. Results: clinic attachment loss (CAL) (P =0.05), the number of tooth loss (P = 0.016) were significantly higher in moderate to severe coronary ASatherosclerosis group, which were more obviously in younger patients and patients with short diabetic duration. Multivariate logistic regression analysis revealed that CAL (OR = 1.231, 95% CI = 1.066-1.214, P = 0.047) and the number of 10-19 missing teeth (OR = 1.604, 95% CI = 1.393-6.555, P = 0.05) were highly associated with moderate to severe coronary AS. Salivary IL-6, and TNF-α levels as well as Porphyromonas gingivalis and Neisseria mucosa were significantly increased in moderate to severe coronary AS group. Conclusions: It was found that both tooth loss and CALparameters of periodontitis were related to the extent of diabetic coronary AS. Saliva inflammatory factors and oral bacteremia may be new biomarkers for moderate to severe coronary AS.